2021
DOI: 10.3389/fmolb.2021.717962
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 and IL-6 Contribute to Corticosteroid Resistance in an OVA and Ozone-induced Asthma Model with Neutrophil Infiltration

Abstract: Exposure to high levels of ozone contributes to insensitivity to glucocorticoids in asthma treatment, but the underlying mechanisms are not known. We built two asthma models: a “T2-high” asthma model was established by ovalbumin (OVA) sensitization/challenge and OVA sensitization/challenge combined with ozone exposure (OVA + ozone) was used to induce airway inflammation with increased numbers of neutrophils to simulate “T2-low” asthma. The expression of T-helper (Th)1/2/17-related cytokines was measured by cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
(58 reference statements)
1
13
0
Order By: Relevance
“…In this sense, acute IL-6 administration induces protein synthesis in myotube cultures [ 38 ]. Another mechanism by which IL-6 can increase muscle mass can be by decreasing the inhibitory effect of glucocorticoid, since the role of IL-6 in experimental asthma-induced glucocorticoid insensitivity has been recently reported [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, acute IL-6 administration induces protein synthesis in myotube cultures [ 38 ]. Another mechanism by which IL-6 can increase muscle mass can be by decreasing the inhibitory effect of glucocorticoid, since the role of IL-6 in experimental asthma-induced glucocorticoid insensitivity has been recently reported [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…TNF participates in training macrophages to rapidly mediate Th2 response following repetitive allergen exposure [ 16 ]. On the other hand, IL-6 orchestrates Th17 cell differentiation and may enhance Th17-driven neutrophilic inflammation in the airways [ 27 , 54 , 73 , 74 , 75 ]. In the present study, we demonstrated that combined pharmacological inhibition of TNF and IL-6 prevents the accumulation of both Th2- and Th1/Th17-cells in the lungs ( Figure 2 A,C and Figure 3 B).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to higher ozone levels could induce the development of glucocorticoid insensitivity during asthma treatment. 12 In this study, the signaling mechanism pertinent to corticosteroid resistance in asthmatic patients with the increased exposure to ozone was delineated. 12 For instance, T2-low asthmatic condition was induced by the infiltration of neutrophils in asthma models by exposure to ovalbumin and ozone.…”
Section: Multiple Signaling Involved In Severe Steroid Resistant (Ssr...mentioning
confidence: 99%
“… 12 In this study, the signaling mechanism pertinent to corticosteroid resistance in asthmatic patients with the increased exposure to ozone was delineated. 12 For instance, T2-low asthmatic condition was induced by the infiltration of neutrophils in asthma models by exposure to ovalbumin and ozone. Inflammatory and pro-inflammatory cytokines expression, lung resistance, etiology of lungs, modulation in the levels of GR and p-GR receptors, Nr3c1 mRNA, (STAT3), (SOCS3), and CXCL1 were ascertained for inducing corticosteroid resistance.…”
Section: Multiple Signaling Involved In Severe Steroid Resistant (Ssr...mentioning
confidence: 99%
See 1 more Smart Citation